Case Report: Vaccine-Induced Immune Thrombotic Thrombocytopenia in a Pancreatic Cancer Patient After Vaccination With Messenger RNA−1273 - Su, Po-Hsu; Yu, Yi-Ching; Chen, Wen-Hsin; Lin, Hsuan-Ching; Chen, Yih-Ting; Cheng, Ming-Huei; Huang, Yen-Min (Frontiers in Medicine, 2021)
Vaccination plays an important role during COVID-19 pandemics. Vaccine-induced thrombotic thrombocytopenia (VITT) is a major adverse effect which could be lethal. For cancer patients, cancer related thromboembolism is another lethal complication. When cancer patients complete their COVID-19 vaccines, the following thromboembolic events will be more complicated. We present a case with newly found pancreatic cancer, who had just received mRNA-1273 (Moderna) vaccination for 12 days. Ischemic stroke and vaccine-induced thrombotic thrombocytopenia were diagnosed. We aggressively treated the patient with steroid, immunoglobulin, and plasma exchange. The titer of anti-platelet factor 4 (PF4) and d-dimer level once became lower but the patient finally expired. The complicated condition of VITT superimposed cancer related thromboembolism was considered. To our knowledge, only a case of mRNA-1273 related VITT was reported and this is the first case of cancer patient reported as VITT after mRNA-1273 vaccination. In conclusion, when cancer patients have increasing needs for vaccination under current COVID-19 pandemics, the possible risk of VITT for cancer patients should be carefully managed. Further studies for risk evaluation of COVID-19 vaccine in cancer patients might be required in the future.